I hope someone can help, I have an equation that I need to rearrange to get the value of y:

.43x + 17.25 + (y/(y+65) *10) = 35

I've managed to get to:

Y = 1.975Y + 128.375 - 0.043xy + 2.795x

but now I'm stumped, could anyone help me please?

I hope someone can help, I have an equation that I need to rearrange to get the value of y:

.43x + 17.25 + (y/(y+65) *10) = 35

I've managed to get to:

Y = 1.975Y + 128.375 - 0.043xy + 2.795x

but now I'm stumped, could anyone help me please?

.43x + 17.25 + (y/(y+65) *10) = 35

I've managed to get to:

Y = 1.975Y + 128.375 - 0.043xy + 2.795x

but now I'm stumped, could anyone help me please?

mgrnoble wrote:I hope someone can help, I have an equation that I need to rearrange to get the value of y:

.43x + 17.25 + (y/(y+65) *10) = 35

I've managed to get to:

Y = 1.975Y + 128.375 - 0.043xy + 2.795x

but now I'm stumped, could anyone help me please?

You did the hard part. Now get all the y terms (including the xy term) on the left with all the other terms on the right. Factor out the y, and divide through.